An advanced human in vitro co-culture model for translocation studies across the placental barrier - Aengenheister, Leonie (Sci Rep, 2018)
Although various drugs, environmental pollutants and nanoparticles (NP) can cross the human placental barrier and may harm the developing fetus, knowledge on predictive placental transfer rates and the underlying transport pathways is mostly lacking. Current available in vitro placental transfer models are often inappropriate for translocation studies of macromolecules or NPs and do not consider barrier function of placental endothelial cells (EC). Therefore, we developed a human placental in vitro co-culture transfer model with tight layers of trophoblasts (BeWo b30) and placental microvascular ECs (HPEC-A2) on a low-absorbing, 3 µm porous membrane. Translocation studies with four model substances and two polystyrene (PS) NPs across the individual and co-culture layers revealed that for most of these compounds, the trophoblast and the EC layer both demonstrate similar, but not additive, retention capacity. Only the paracellular marker Na-F was substantially more retained by the BeWo layer. Furthermore, simple shaking, which is often applied to mimic placental perfusion, did not alter translocation kinetics compared to static exposure. In conclusion, we developed a novel placental co-culture model, which provides predictive values for translocation of a broad variety of molecules and NPs and enables valuable mechanistic investigations on cell type-specific placental barrier function.